Representations of Gharb Al-Andalus in selected travel writing, historical fiction and journalism (1787-1989) - Gryspeerdt, Juliet (2020)
This study investigates how Gharb (Western) Al-Andalus is represented in a selection of texts written in Portuguese, English, French and Spanish, dating from the Romantic period, beginning in the late 1780s, up until the late twentieth century. The first chapter examines British and French travel writing up until the late nineteenth century, while the second investigates nineteenth-century historical fiction which draws on travel writing. The third chapter focuses on the early twentieth century as an age of politicisation, looking at Portuguese journalism and British travel writing, whereas the fourth moves to the late twentieth century to examine José Saramago’s travel writing and historiographical metafiction.